POLITICAL STRUGGLE IN MODERN WORLD - Alexandr A. Borshch (Сравнительная политика)
The article deals with the notion of political struggle and its purpose, direction, and forms, which are pursued through parliamentary channels, revolutionary means or guerrilla (national liberation) movements. The author separates fight for breaking the dominating social and economic system and competition between political groupings within the existing formation. He analyses both examples of lawful political competition and actions going beyond legal field. He also mentions that widely discussed hypothesis of disappearance of revolutions ignores remaining social tensions, which even grow due to the development of globalization.